Customer Satisfaction with The Product Quality and Service of Meatball Celebes Restaurant in Makassar City - Aslina Asnawi; Siti Nurlaelah; Inas Nabilah Apriana Mansur; Besse Rizky Fortuna; Yulia Rahmaniar (Faculty of Animal Science, Universitas Brawijaya, 2023)
In the objective of meeting the need for animal protein, the Maiwa Breeding Center (MBC) carried out diversification of its processed chicken meat products in the form of crispy chicken. This study aimed to analyze the level of consumer satisfaction with the quality and services of the products provided by Meatball Celebes Restaurant. The data were collected from 98 respondents who were randomly selected from each predetermined area using an online questionnaire in the form of google form format during the COVID-19 pandemic. Data were further analyzed using IPA (Importance Performance Analysis) and CSI (Customer Satisfaction Index) analysis. The results revealed that the product quality of the Celebes meatball restaurant, which is the product suitability attribute, became an important attribute, so it needed to be improved. Furthermore, function, reliability, and quality attributes must be maintained because they are important categories, whose performance are currently good. The attributes of physical conditions including the cleanliness, parking areas, and complete facilities are the main priority categories to be improved. The ability to provide reliable services, performance needs to be maintained because it has been good and is considered important by consumers. The responsiveness attribute, however, is a low priority to be improved. Based on the CSI analysis, the level of consumer satisfaction, which is the quality of the product, obtained a value of 0.79, while the service obtained a value of 0.78, thus categorized as satisfied. Therefore, these aspects need to be more improved in order to become very satisfied.